2015
DOI: 10.1115/1.4030897
|View full text |Cite
|
Sign up to set email alerts
|

A Systematical Study of the Influence of Blade Length, Blade Width, and Side Channel Height on the Performance of a Side Channel Pump

Abstract: Two modular side channel pump models have been investigated both numerically and experimentally. For both modular designs, different side channels and impellers could be studied, with the aim to get information about the influence of the different geometries on the performance and the inner flow phenomena of the pump. By understanding the geometry influences, statements about the design process of the pump are possible. Changes of the geometry of the side channel or the impeller affect the flow in both compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 5 publications
0
31
0
Order By: Relevance
“…The fluid flows in a straight line to the pump inlet, and kinetic energy is converted into pressure energy and the head is developed after numerous reentries into the rotating impeller and creates a high momentum exchange from the blade to the fluid and leaves through the outlet of the pump in a helical or spiral form. This effect causes an upturn in the pump head (pressure) from about 5 to 10 times better than the impeller of a common pump rotating at the same speed . The electrical energy produced by the pump motor is converted to mechanical energy.…”
Section: Flow Mechanismmentioning
confidence: 99%
See 3 more Smart Citations
“…The fluid flows in a straight line to the pump inlet, and kinetic energy is converted into pressure energy and the head is developed after numerous reentries into the rotating impeller and creates a high momentum exchange from the blade to the fluid and leaves through the outlet of the pump in a helical or spiral form. This effect causes an upturn in the pump head (pressure) from about 5 to 10 times better than the impeller of a common pump rotating at the same speed . The electrical energy produced by the pump motor is converted to mechanical energy.…”
Section: Flow Mechanismmentioning
confidence: 99%
“…This makes the flow of fluids in this kind of pump very complex as depicted in Figure . The pump does not transport the same volume of fluid that enters out; meanwhile, some portion of the fluid moves back into interrupter gap and is conveyed by the pressure side of the blade to the suction side . Shirinov and Oberbeck explained the movement of gas in the side channel pump.…”
Section: Flow Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that there was an optimum chevron angle of around 30 0 [13]. Fleder and Böhle studied the effect of the variation of the blade length, blade width, and side channel height by the help of dimensionless parameters [14]. Karanth et al used CFD analysis to enhance the performance of regenerative pump.…”
Section: Introductionmentioning
confidence: 99%